No mud, no lotus : The art of transforming suffering - Thich, Nhat Hanh (Parallax Press, 2014)
In this book, Thich Nhat Hanh teaches that suffering is an essential part of life, but it can be transformed into peace, joy, and enlightenment. Using the metaphor "no mud, no lotus," he explains that just as a beautiful lotus grows from muddy water, happiness can arise from embracing and understanding suffering. Through mindfulness practices, breathing techniques, and gentle reflections, the book offers practical ways to deal with pain, develop compassion, and find inner freedom.